ANALYSIS OF ANIES BASWEDAN’S RHETORIC AS A POLITICAL COMMUNICATION STRATEGY TO ATTRACT PUBLIC ATTENTION - Winda Kustiawan; Faiz Ahmad Zidan; Nanda Risani Raqiqah; Dwi Asyila Sabrina Br. Saragih (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2025)
This study aims to analyze Anies Baswedan’s political communication style and its influence on public appeal, particularly among the younger generation. Although he lost in the 2024 Presidential Election, Anies remains a respected and prominent public figure due to his rhetorical, intellectual, and humanist approach to communication. Using a qualitative method and discourse analysis approach, this research examines how Anies establishes emotional connections with the public through speeches, discussions, social media, and the implementation of populist policies. The findings reveal that Anies’s calm, educational, and persuasive communication style is not only effective in delivering political messages but also serves as a form of intellectual da’wah that promotes public literacy and active civic participation, especially among youth.